Visible foliar injury as a tool for the assessment of surface ozone impact on native vegetation: a case study from the Jizerské hory Mts - L. Matoušková; R. Novotný; I. Hůnová; V. Buriánek (Journal of Forest Science, 2010)
Surface ozone is considered to be a very phytotoxic gaseous air pollutant. Its negative impacts at both the cell and the organ level have been shown, mainly as a result of experiments. However, the demonstration of ozone negative impacts on native plants is not explicit. An assessment of ozone impact on vegetation and ecosystems using indicators based on ambient ozone concentrations is insufficient and assessment techniques based on internal ozone dose and on real plant damage are more appropriate. Such a possible technique is the mapping of ozone visible symptoms due to ozone influence. The ICP-Forest method concerning ozone visible symptoms and the assessment of ozone influence were applied for the purposes of this case study. The visible symptoms are characterized by a few typical signs. Nevertheless, the identification of visible symptoms in native conditions can be problematic and misleading conclusions could be drawn. Therefore it is necessary to complete the identification of visible symptoms with a validation in order to confirm ozone as the cause of plant injury.